2009
DOI: 10.1002/ppsc.200800016
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the Mechanical Properties of Powdered Agricultural Products and Sugar

Abstract: Grain, forage cereals and different types of flour are commonly stored in silos. Their behavior within these structures is mainly governed by their mechanical properties. Since their advent, numerical methods have increasingly been used in silo design. However, the results obtained using these methods strongly depend on the variables employed to define the materials stored. Since the literature provides little information on the variables required for modeling the behavior of agricultural powdered materials, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
23
0
5

Year Published

2012
2012
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 18 publications
3
23
0
5
Order By: Relevance
“…These differences ranged between 183% for 'Camacho' wheat and 241% for sunflower. Similar differences were observed by Rusinek and Molenda (2007) for rapeseed and by Ramirez et al (2009) when using the same types of surfaces with powdered agricultural products such as confectioner sugar and granulated sugar. Very small values (0.135±0.002) for the coefficient of friction between wheat and smooth galvanized steel were obtained by Molenda et al (2002a).…”
Section: Discussionsupporting
confidence: 66%
See 2 more Smart Citations
“…These differences ranged between 183% for 'Camacho' wheat and 241% for sunflower. Similar differences were observed by Rusinek and Molenda (2007) for rapeseed and by Ramirez et al (2009) when using the same types of surfaces with powdered agricultural products such as confectioner sugar and granulated sugar. Very small values (0.135±0.002) for the coefficient of friction between wheat and smooth galvanized steel were obtained by Molenda et al (2002a).…”
Section: Discussionsupporting
confidence: 66%
“…However, they could not find a clear explanation for this case. Ramirez et al (2009) observed that the values for the angle of internal friction were higher when using triaxial tests than those obtained from direct shear tests for tests conducted using powdered agricultural products and sugar.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…Its design ( Figure 2) was based on the Casagrande shear box (CG WFT) which allows relative displacement of parts of the box to be controlled [52,53]. Direct shear tests were used to determine the particle-to-wall friction coefficient.…”
Section: Casagrande Shear Box -Cg Wftmentioning
confidence: 99%
“…However, standard characterization methods used for flow properties of common granular solids are not always suitable for biomass materials. A significant problem is that conventional shear testers have been mainly developed for measuring frictional and cohesive properties of bulk solids with non-fibrous rigid and generally homogeneous particle shapes as well as with particle top sizes below a few millimeters [22][23][24]. Few biomass materials have particle size, stiffness and shape distributions that meet these requirements.…”
Section: Introductionmentioning
confidence: 99%